Urgensi Legalitas Pelaksanaan Lelang Online Melalui Media Sosial Instagram - Cut Maidina Ananda Putri; Sutiarnoto -; Jelly Leviza; Maria Kaban (Ilmu Hukum Prima (IHP), 2021)
The implementation of auctions through Instagram social media often does not provide legal certainty for the parties participating in the auction because many in its implementation are not in accordance with the regulation of the Minister of Finance Number 213/PMK.06/2020 concerning auction implemention guidelines. So that in its implementation can cause disadvantage for the parties carrying out the auction. The research used descriptive analytical juridical normative method. Primary data and secondary data were obtained from library research and field research. The result of the research shows that the legal status of the Instagram account @usedbapeofficial was not an official auction house because it did not meet the requirements as an auction house, which should be in the form of limited liability company and obtaining permission form the Minister. Legal certainty for the owner of the goods has been carried out by @usedbapeofficial in the form of the payment proceeds being transferred to only one account, namely Kenneth Lee’s account as the account owner but does not provide legal certainty regarding when the owner of the goods will receive payment for the goods he auctions, legal certainty for the auction winner has been provides in the form of information that is listed in accordance with the format filled in by the owner of the goods. Legal protection for the owner of the goods is given in the form of holding funds in the @usedbapeofficial account until the goods are received by the buyer, while for the auction winner the legal protection is in the form of preventive and repressive legal protection. The conclusion of this research is the legal status of Instagram account @usedbapeofficial is not an official auction house. Legal certainty for the owner of the goods and the auction winner has not been fulfilled because most of the implementation of the auction on the Instagram account @usedbapeofficial do not comply with the provisions in the regulations of the Minister of Finance Number 213/PMK.06/2020 concerning auction implementation guidelines. Legal protection for the owner of the goods provided by @usedbapeofficial in the form of money auction sales is accommodated in one account, while legal protection for the auction winner has not been fully fulfilled because in its implementation legal protection is not provided by @usedbapeofficial in full to the injured party. It is recommended to @usedbapeofficial to improve the auction procedure into a buying and selling account with an auction mechanism and register its business as a Limited Liability Company, it is suggested to the government to update the regulations governing auction activities through social media, especially Instagram.